Local Revenue And Financial Independence On Economic Growth Through Capital Expenditure - Ni Putu Yuliana Ria Sawitri; Luh Putu Virra Indah Perdanawati; Ni Nyoman Sudiyani; Made Setini (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
This study aims to analyze changes in regional income and financial independence of regional economic growth with capital expenditure as a variable intervention in Denpasar City in 2017-2019. This exploration technique is a graphic subjective strategy with the cooperation of region and regional government in Denpasar 2017-2019. This study used the purposive sampling method. Test results show that the Regional Revenue directly has a positive effect on regional economic growth while financial independence does not directly affect regional economic growth, and capital expenditure cannot mediate local income growth and financial independence on economic growth.